THE EFFECT OF GINGER SOFTWARE ON THE TENTH GRADE STUDENTS’ WRITING SKILL - Ika - Restika; imtihan - Hanim; Dyah Supraba Lastari (Globish: An English-Indonesian Journal for English, Education, and Culture, 2021)
The aim of the research was to investigate whether Ginger Software can be used to improve the writing skill of the tenth grade students at SMK Ki Hajar Dewantoro. The participants of this research were 64 students, which were classified into the controlled class and the experimental class. The design used was quasi-experimental study and the instruments of this research consisted of pre-test and post-test. The result showed that using Ginger Software was effective and appropriate to improve students’ writing skill. It could be seen from the average of post-test result in experimental class was 75.90, and the average of pre-test was 65.06. Meanwhile, the average of post-test result in controlled class was 66, and the average of pre-test was 59.21. The result of the t-test of post-test also showed that there was a significant difference between experimental and controlled class, t-count of ɑ = 5% df = 62 was 3.48 and for t-table was 2.00. The calculation proved that t-value was higher than t-table. It means that H1 is accepted and H0 is rejected. It can be concluded that Ginger Software gave significant effect on improving students’ writing skill.  Key words: Ginger Software, Writing Skill